ANALYSIS OF PROBLEMS OF CONTROL SYSTEM OF INFORMATION SECURITY OF ORGANIZATION - Сафронов, Александр Сергеевич (Eastern-European Journal of Enterprise Technologies, 2010)
In this work the problems and requirements for information security management system for organizations are analyzed. The life cycle of information security management system is considered.